ÖMER EL-HERMÎ'NİN ARAP DİLİ GRAMERİNE İLİŞKİN GÖRÜŞLERİ - AYDIN, MEHMET (Fırat Üniveristesi, 2018)
Dil insanlar arasındaki iletişimi sağlayan en önemli olgudur. Her dilin kendine göre gelişim süreçleri vardır. Arap dilinin gelişmesinde en etkili faktör Kur'ân-ı Kerim'in Arapça olarak indirilmesidir. Bu nedenle Arap dili, çoğu ilim adamının ilgi odağı olmuştur. Ancak Arap olmayan milletlerin ve ırkların Müslüman olmasıyla kabul ettikleri dinin kutsal kitabının dili olan Arapçayı öğrenmeye çalışmalarıyla dil hataları ortaya çıkmıştır. İslam âlimleri Arap dilini bu dil hatalarından kurtarmak için nahvin kural ve kaidelerini tespit edip korumaya önem vermişler ve bu konuda yüzlerce eser telif etmişlerdir. Biz bu çalışmamızda yukarda zikrettiğimiz o eserlerden biri olan el-Muharrar fi'n-Nahv adlı kitabı ve bu eserin müellifi Ömer b. İsa b. İsmail el-Hermî'nin hayatını, ahlakını, ilmi kişiliği ve nahiv ilmi ile ilgili görüşlerini tahlil etmeye çalıştık.

Language is the most important thing that provides communication between people. Each language has its own development process. The factor that plays the most effective role in the development of the Arabic language is that the Qur'an is Arabic. For this reason, the Arabic language has become the focus of most scholars. However, with non-Arab nations and races becoming Muslims, language mistakes have arisen as they have tried to learn the Arabic language of Islam, which they have recently met. Islamic scholars have attached great importance to identifying and protecting the nahib rules and bases in order to save the Arabic language from these language mistakes. In fact, hundreds of works have been copyrighted. We present our research we already mentioned above, is one of those works, the hand of al-Muharar fin-Nahv for his work and the work of the author Eco Industrial Park'y his life, morality, personality and nahiv their opinion of scientific knowledge, we tried to analyze.
Omar el-Hermi's opinions related to Arabic grammar
Keywords: Din